Policy discourses in Malaysian education a nation in the making - Malakolunthu, Suseela; Rengasamy, Nagappan C. (Routledge critical studies in Asian education, 2017)
Since independence in 1957, Malaysia has become a globally-recognised industrial trading partner. With a 60% Muslim population, it also enjoys the reputation of being a moderate and peaceful nation. This book analyses the education policies that have been formulated and implemented in Malaysia since independence. It demonstrates how these policy enactments have influenced the nation's growth and transformation, and the challenges faced in creating a model of equity and multicultural co-existence among its racially and ethnically diversified people. Shedding light on these issues, it points towards the major mending that is needed for Malaysia to become a truly developed nation.